Customer Relationship Management Strategy in Mobile-Based E-Commerce Platform Development to Increase Purchase Interest - Br Purba, Yunita Dana; Haraha, Aninda Muliani (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
The demands of technological developments trigger every company to be able to increase competitive advantages in order to create a smooth business process. Customer satisfaction in comparing expectations before making a transaction with the service directly felt by a customer is one of the elements that affect how succesful. Therefore, this study develops and implements a mobile-based e-commerce system equipped with a customer relationship management feature that aims to increase the involvement of interest and product purchases at the Tarigan Clothing Store so that it can provide very significant additional value in a product marketing process. This mobile-based e-commerce information system application also utilizes javascript technology as its interface design. The use of javascript is considered to facilitate access to the latest features in the e-commerce application that is built because of the high existence of javascript which continues to develop according to technological advances. This mobile-based e-commerce application is expected to provide wider reach, convenience and become a more effective marketing tool for customers and Tarigan Clothing Store so that it can provide significant benefits for both parties and create a more comfortable and efficient shopping process.